A Causal Relationship of Smart Tourism Technology, Experience, Engagement, and Behavioural Intention of Museum Visitors in Thailand - Pongsata, Pattaramook; Pooripakdee, Santidhorn; Jadesadalug, Viroj (Rajapark Journal, 2024)
Smart tourism technology is implemented by the tourism industry as a new concept to enhance the visitor experience, engagement, and behavioral intentions. However, research that explores the relationship between smart tourism technology and these variables is still limited, especially in the context of museums. Therefore, this article aims to study the influence of smart tourism technology in museums on the experience, engagement, and behavioral intention of museum visitors in Thailand. This research is quantitative research using a questionnaire as a tool. Data was collected from Thai museum visitors aged 18 to 59 who have used smart tourism technology in the museum, with a total of 400 samples. The frequency, percentage, and model fit index for structural equation modeling are the statistics utilized in data analysis. The research findings indicate that 1) smart tourism technology in museums positively influences visitor experiences and engagement. 2) Visitor experience positively influences visitor engagement.3 Visitor engagement positively influences visitors’ behavioral intentions. 4) Visitor engagement mediates the relationship between smart tourism technology in museums and behavioral intentions. 5) Visitor experience and engagement mediate the relationship between smart tourism technology in museums and behavioral intentions.